Mechanism of cloned ATP-sensitive potassium channel activation by oleoyl-CoA. - Gribble, F; Proks, P; Corkey, B; Ashcroft, F (1998)
Insulin secretion from pancreatic beta cells is coupled to cell metabolism through closure of ATP-sensitive potassium (KATP) channels, which comprise Kir6.2 and sulfonylurea receptor (SUR1) subunits. Although metabolic regulation of KATP channel activity is believed to be mediated principally by the adenine nucleotides, other metabolic intermediates, including long chain acyl-CoA esters, may also be involved. We recorded macroscopic and single-channel currents from Xenopus oocytes expressing either Kir6.2/SUR1 or Kir6. 2DeltaC36 (which forms channels in the absence of SUR1). Oleoyl-CoA (1 microM) activated both wild-type Kir6.2/SUR1 and Kir6.2DeltaC36 macroscopic currents, approximately 2-fold, by increasing the number and open probability of Kir6.2/SUR1 and Kir6.2DeltaC36 channels. It was ineffective on the related Kir subunit Kir1.1a. Oleoyl-CoA also impaired channel inhibition by ATP, increasing the Ki values for both Kir6.2/SUR1 and Kir6.2DeltaC36 currents by approximately 3-fold. Our results indicate that activation of KATP channels by oleoyl-CoA results from an interaction with the Kir6.2 subunit, unlike the stimulatory effects of MgADP and diazoxide which are mediated through SUR1. The increased activity and reduced ATP sensitivity of KATP channels by oleoyl-CoA might contribute to the impaired insulin secretion observed in non-insulin-dependent diabetes mellitus.